Development of new strategies for early diagnosis of mucormycosis from bench to bedside. (December 2014) - Walsh, Thomas J.; Skiada, Anna; Cornely, Oliver A.; Roilides, Emmanuel; Ibrahim, Ashraf; Zaoutis, Theoklis; Groll, Andreas; Lortholary, Olivier; Kontoyiannis, Dimitrios P.; Petrikkos, George
Summary: Early diagnosis and initiation of amphotericin B (AmB) for treatment of mucormycosis increases survival from approximately 40% to 80%. The central objective of a new study of the European Confederation of Medical Mycology (ECMM) and the International Society for Human and Animal Mycology (ISHAM) Zygomycosis Working Group is to improve the clinical and laboratory diagnosis of mucormycosis. The diagnostic tools generated from this study may help to significantly improve survival from mucormycosis worldwide. The study has three major objectives: to conduct a prospective international registration of patients with mucormycosis using a well‐established global network of centres; to construct a predictive risk model for patients at risk for mucormycosis; and to establish an international archive of specimens of tissues, fluids, and organisms linked from the patients enrolled into the registry that will be used for development of leading edge molecular, proteomic, metabolic and antigenic systems for mucormycosis.